Multi-Axial Clamp Assemble - Zamzuri, Hamedon (2016)
External skeletal fixator systems are used on fractured bones or joints during osteosynthesis typically for more serious injuries involving multiple or compound fractures. Pins are drilled through a patient's skin and into a fractured bone. Clamps secure the pins to a common connecting rod, creating a rigid frame that immobilizes the bone.